Pengaruh Arsitektur Modern Pada Desain Masjid Istiqlal - Rahil Muhammad Hasbi; Wibisono Bagus Nimpuno (Vitruvian : Jurnal Arsitektur, Bangunan dan Lingkungan, 2019)
Modern architecture in its golden age has given a lot of influences to many architectures around the world. The spread of modern architecture at that time could not be stopped and became a style that is widely used throughout the world including IndonesiaThe influence of modern architecture emerged in Indonesia during the Dutch colonial occupation. European architects at that time introduced classical European architecture and modern architecture to Indonesian society. During the Colonial occupation and at the beginning of Indonesian independence, European architects designed public buildings such as government buildings, places of worship( like mosques and churches) and commercial buildings as well as several residences using classical European architectural and modern architecture.As the example that we can still see now is the Istiqlal Mosque in Jakarta, Indonesia, which was designed by architect Friedrich Silaban who self-taught modern architecture. The design of the Istiqlal mosque at a glance looks very much influenced by modern architecture, although domes and tower as a characteristic of Middle East architecture is still been used.The mosque as a whole is designed to look monumental which emphasized the used of a mixture of modern architecture styles.